THEORETICAL FOUNDATIONS OF ENTREPRENEURIAL DEVELOPMENT - Javxarov Alisher Bahodirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article discusses scientific research conducted on a new theory of entrepreneurship development, the views of scientists on the theory of entrepreneurship development, the results of scientific research at universities, and modern knowledge.